Pseudoscaffolds and anchoring proteins: the difference is in the details - Aggarwal-Howarth, Stacey (Biochem Soc Trans, 2017)
Pseudokinases and pseudophosphatases possess the ability to bind substrates without catalyzing their modification, thereby providing a mechanism to recruit potential phosphotargets away from active enzymes. Since many of these pseudoenzymes possess other characteristics such as localization signals, separate catalytic sites, and protein–protein interaction domains, they have the capacity to influence signaling dynamics in local environments. In a similar manner, the targeting of signaling enzymes to subcellular locations by A-kinase-anchoring proteins (AKAPs) allows for precise and local control of second messenger signaling events. Here, we will discuss how pseudoenzymes form ‘pseudoscaffolds’ and compare and contrast this compartment-specific regulatory role with the signal organization properties of AKAPs. The mitochondria will be the focus of this review, as they are dynamic organelles that influence a broad range of cellular processes such as metabolism, ATP synthesis, and apoptosis.